Yeast require an Intact Tryptophan Biosynthesis Pathway and Exogenous Tryptophan for Resistance to Sodium Dodecyl Sulfate - McClellan, Amie Jo; Ammons, Laura M.; Bingham, Logan R.; Callery, Sarah; Corley, Elizabeth; Crowe, Katherine A.; Lipton, Jennifer K.; Mendez, Carlos A.; Morrison, Tessalyn; Rallis, Claudia (Journal of Student Research, 2015)
Sodium Dodecyl Sulfate, or SDS, is an anionic detergent with widespread use in industrial and household cleaning products, scientific laboratories, and personal care products such as toothpaste and shampoo. The potential toxicity of SDS has been well-characterized in whole organism studies and its potential effects on the environment continue to be studied. Herein, we undertake a chemical-genetic screen to explore whether low concentrations of SDS have any discernible effects at the cellular level. Our screen of the homozygous diploid yeast deletion collection identified numerous gene deletions that confer sensitivity to SDS. Subsequent bioinformatic and biological analyses reveal that yeast unable to synthesize tryptophan are especially sensitive to the presence of SDS. Interestingly, even wild-type yeast with an intact tryptophan biosynthetic pathway exhibit growth defects in the presence of SDS on media lacking tryptophan. Altogether, we have shown that low levels of SDS, primarily through effects on tryptophan availability, impact the basic cell biology of a eukaryotic cell.